Impact of Community College Student Debt Levels on Credit Accumulation. Issue 1 (May 2017) - Baker, Dominique J.; Doyle, William R.
Most community college students do not borrow to pay for their education. However, in recent years more students are borrowing and, when they borrow, accumulating large amounts of debt. To help clarify whether increased debt burdens are aiding community college students or harming them, we explore the impact of borrowing on academic credit hour accumulation. Using data from the Education Longitudinal Study 2002–2012, we provide multiple estimates of the impact of borrowing on credit hour attainment among community college students. Standard estimates suggest that community college students who borrow complete fewer credit hours than students who do not borrow, although the influence is relatively small (about two credits two years after enrollment). Instrumental variables estimates suggest that the impact of borrowing on credits attained is not significant two years after enrollment but is substantial eight years after enrollment (allowing students multiple enrollment spells).